Exposure to immersive relaxing virtual environments for hospitalized patients - Pereira, Miguel (2024)
Hospitalized patients are often characterized by various stress factors that can have an impact on their mental health and hospital experience. Improving the quality of life of these bedridden patients is an important task by relieving their anxiety, reducing their pain, and encouraging them in their fight against disease. Virtual reality has already been proved to be a novel and promising tool to improve the quality of life of hospitalized patients. Therefore, the purpose of this chapter is to focus on studies that gave evidence to the feasibility of virtual reality relaxation therapies for hospitalized patients, which virtual reality relaxation therapies are most used, and the benefits and limitations of this type of intervention.